Courses
Courses for Kids
Free study material
Free LIVE classes
More LIVE
Join Vedantu’s FREE Mastercalss

# The orthogonal projection of the point A with position vector (1,2,3) on the plane 3x-y+4z=0 is [a] $\left( -1,3,-1 \right)$[b] $\left( -\dfrac{1}{2},\dfrac{5}{2},1 \right)$[c] $\left( \dfrac{1}{2},\dfrac{-5}{2},-1 \right)$[d] $\left( 6,-7,-5 \right)$ Verified
360k+ views
Hint: The normal vector of the plane ax+by+cz = d is (a,b,c). So choose the point P(x,y,z) PA is parallel to the normal vector. P also satisfies the plane equation. This will give you a system of three equations. Solve the system using any method. This will give the coordinates of the point P.

We know that the normal vector of the plane ax+by+cz = d is (a,b,c)
Here a = 3, b = -1, c = 4 and d = 0.
Hence the normal vector(N) of the plane is $3\widehat{i}\text{ - }\widehat{j}\text{ + }4\widehat{k}$
Let P(x,y,z) be the project of A on the plane 3x-y+4z=0
Since P lies on the plane, we have
3x-y+4z = 0 (i)
Also $\overrightarrow{AP}=\left( x-1 \right)\widehat{i}\text{ +}\left( y-2 \right)\widehat{j}\text{ + }\left( z-3 \right)\widehat{k}$
Since $AP\parallel N$we have
\begin{align} & \dfrac{x-1}{3}=\dfrac{y-2}{-1}=\dfrac{z-3}{4}=t\text{ (say)} \\ & \Rightarrow x=3t+1,y=2-t,z=4t+3 \\ \end{align}
Now we have
Put the value of x,y and z in equation (i) we get
\begin{align} & 3\left( 3t+1 \right)-\left( 2-t \right)+4\left( 4t+3 \right)=0 \\ & \Rightarrow 9t+3-2+t+16t+12=0 \\ & \Rightarrow 26t+13=0 \\ \end{align}
Subtracting 13 from both sides, we get
\begin{align} & 26t+13-13=0-13 \\ & \Rightarrow 26t=-13 \\ \end{align}
Dividing both sides by 26, we get
\begin{align} & \dfrac{26t}{26}=\dfrac{-13}{26} \\ & \Rightarrow t=-\dfrac{1}{2} \\ \end{align}
Hence we have
\begin{align} & x=3t+1=\dfrac{-3}{2}+1=\dfrac{-1}{2} \\ & y=2-t=2-\left( -\dfrac{1}{2} \right)=2+\dfrac{1}{2}=\dfrac{5}{2} \\ & z=4t+3=4\left( -\dfrac{1}{2} \right)+3=-2+3=1 \\ \end{align}
Hence $P\equiv \left( \dfrac{-1}{2},\dfrac{5}{2},1 \right)$ is the point of the orthogonal projection of A.

Note: Alternatively we have, the equation of the line perpendicular to the plane passing through A in parametric form is $x=3t+1,y=-t+2,z=4t+3$ where t is the parameter.
The line intersects the plane at point P(t)
Then we have
\begin{align} & 3\left( 3t+1 \right)-\left( 2-t \right)+4\left( 4t+3 \right)=0 \\ & \Rightarrow 9t+3-2+t+16t+12=0 \\ & \Rightarrow 26t+13=0 \\ & \Rightarrow 26t=-13 \\ & \Rightarrow t=-\dfrac{1}{2} \\ \end{align}
Hence
\begin{align} & P\equiv \left( 3\times \dfrac{-1}{2}+1,-\dfrac{-1}{2}+2,4\times \dfrac{-1}{2}+3 \right) \\ & \Rightarrow P\equiv \left( \dfrac{-1}{2},\dfrac{5}{2},1 \right) \\ \end{align}
Last updated date: 25th Sep 2023
Total views: 360k
Views today: 6.60k